2001
DOI: 10.1046/j.1442-9993.2001.01112.x
|View full text |Cite
|
Sign up to set email alerts
|

Seed hoarding by rodents of the Monte Desert, Argentina

Abstract: Food storage is an important adaptation of several animal species to the temporally variable or unpredictable food supplies that are typical of desert environments. In the present study, whether Eligmodontia typus and Graomys griseoflavus inhabiting sand dunes in the Monte desert displayed scatter-hoarding was investigated. Both rodent species prepared surface caches by digging small holes (1-3 cm deep) in the soil. Caches were partially covered with sand and dry leaves, which meant that all of the cache sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 34 publications
2
44
0
Order By: Relevance
“…Rodents mostly moved acorns short distances, in agreement with many other studies of scatter-hoarding rodents in a variety of habitats (e.g., Sork 1984;Jensen 1985;Jensen and Nielsen 1986;Giannoni et al 2001;Li and Zhang 2003;Cheng et al 2005;Iida 2006;Takahashi et al 2006). Acorn weight aVected both dispersal and caching behavior.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Rodents mostly moved acorns short distances, in agreement with many other studies of scatter-hoarding rodents in a variety of habitats (e.g., Sork 1984;Jensen 1985;Jensen and Nielsen 1986;Giannoni et al 2001;Li and Zhang 2003;Cheng et al 2005;Iida 2006;Takahashi et al 2006). Acorn weight aVected both dispersal and caching behavior.…”
Section: Discussionsupporting
confidence: 66%
“…This was somewhat surprising since most studies have shown that rodents prefer to forage under shrubs where they are well protected from predators rather than under trees (Jensen and Nielsen 1986;Alcántara et al 2000;Rey et al 2002;Fedriani and Manzaneda 2005; but see Muñoz and Bonal 2007). In addition, rodents frequently disperse seeds disproportionately to the cover of shrubs (Giannoni 2001;Vander Wall 2001;Li and Zhang 2003;Takahashi et al 2006).…”
Section: Discussionmentioning
confidence: 90%
“…the physical disturbance caused by herbivory) influences plant community structure and diversity in the Monte Desert (Tognelli , 1999). A common foraging behavior in deserts which is associated with ephemeral and unpredictable food resources is food hoarding, and it has been reported for two of the dominant rodents, the silky mouse, E. typus and the common pericote, G. griseoflavus (Giannoni et al, 2001). Taraborelli et al (2003) observed that the plant cover affects the foraging activity of rodents because both consumption and a higher number of caches occur below shrubs.…”
Section: Plant-animal Interactionsmentioning
confidence: 97%
“…In arid shrublands where individual shrubs are widely spaced, wind-blown or watertransported soil, nutrients, litter and seeds accumulate under these long-lived shrubs or trees, producing a heterogeneous environment that exerts great influence on basic ecosystemic processes (Pucheta et al, 2006;Reynolds et al, 1999;Schlesinger and Pilmanis, 1998;Zaady et al, 1998). Moreover, many animals also cause seed redistribution by activities such as predation (Campos and Ojeda, 1997;Herrera, 1995;Milton and Dean, 2001;Villagra et al, 2002), burrowing, digging and seed hoarding (Armesto and Rozzi, 1989;Giannoni et al, 2001).…”
Section: Introductionmentioning
confidence: 99%